A comparison study of Quick60 and reading recovery instruction : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - MacDougall, Bridget Alexandra (Massey University, 2016)
New Zealand has a national system of early reading intervention called Reading Recovery. This intervention is available to children after a year at school if they are seriously underachieving in reading. There has, however, been concern that the intervention has not achieved its aim of bringing underachieving readers up to class average. Results of international literacy surveys consistently indicate a wide gap between the best and poorest readers. Some critics have argued that a key reason for the gap is a lack of focus on the explicit teaching of phonologically-based skills in Reading Recovery and that other interventions could be more effective. One intervention that has been suggested is Quick60, a New Zealand developed literacy intervention for underachieving children that is taught in small groups and emphasises the teaching of phonologically-based skills. One aim of the present study was to assess the efficacy of Quick60 relative to Reading recovery. A second aim was to consider whether Quick60 could be of equal efficacy but more cost-effective than Reading Recovery which is taught on an individual basis and is whole language in approach. The comparison study of Quick60 and Reading Recovery took place in two schools and involved 30 children. Children were assessed on a number of language and literacy measures before and after 13 weeks of instruction. The results of the study indicated that both the Quick60 and Reading Recovery children made gains but no more than did the control group.
Keywords: Reading; Remedial teaching; Reading (Elementary); Quick60; Reading Recovery; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::Subject didactics